2005
DOI: 10.1111/j.1601-0825.2004.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modified acidic soft drinks on enamel erosion

Abstract: Modification of the test soft drinks with low concentrations of calcium or a combination of calcium, phosphate and fluoride may exert a significant protective potential with respect to dental erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
2
16

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 42 publications
5
95
2
16
Order By: Relevance
“…Citric acid is an acid that is widely contained in soft drinks and has a high demineralization potential [11]. A study conducted by Lussi et al and Attin et al showed that citric acid acts as a chelator agent that can bind calcium on the surface of an enamel, which indicates the potential demineralization of acidic beverages in everyday life [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citric acid is an acid that is widely contained in soft drinks and has a high demineralization potential [11]. A study conducted by Lussi et al and Attin et al showed that citric acid acts as a chelator agent that can bind calcium on the surface of an enamel, which indicates the potential demineralization of acidic beverages in everyday life [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Citric acid is an acid that is widely contained in soft drinks and has a high demineralization potential [11]. A study conducted by Lussi et al and Attin et al showed that citric acid acts as a chelator agent that can bind calcium on the surface of an enamel, which indicates the potential demineralization of acidic beverages in everyday life [11,12]. Michele et al in his study showed that immersion of citric acid (in vitro) pH 4 for 150 seconds was equal to 40 minutes of enamel exposure with orange juice (in situ), and there was a significant decrease in surface hardness value after immersion in an acidic solution [13].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the reduction of the erosive potential, the modification of drinks might lead to an alteration in the taste [3,29,30]. As the taste is an important criterion for a successful dietary modification [30] the authors of the present study were asked for estimation of the taste of the viscosity-modified beverages compared to the original decarbonized ones.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the addition of 1 mmol/l Ca or a combination of 0.5 mmol/l Ca, 0.5 mmol/l P and 0.0031 mmol/l F resulted in a 38 -64% reduction of erosive enamel loss [3].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation